2019
DOI: 10.1093/jac/dkz415
|View full text |Cite
|
Sign up to set email alerts
|

MDR Salmonella enterica serovar Typhimurium ST34 carrying mcr-1 isolated from cases of bloodstream and intestinal infection in children in China

Abstract: Objectives Children are vulnerable to Salmonella infection due to their immature immune system. Cases of infection with mcr-1-harbouring Salmonella in child inpatients have not been reported in China before. Methods Salmonella isolates from gastroenteritis and bacteraemia were screened using primers targeting mcr-1. Complete genome sequences of mcr-1-harbouring isolates were determined using the PacBio RS II platform. The tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 19 publications
3
27
1
Order By: Relevance
“…According to our latest data related to more than 3,800 foodborne Salmonella recovered in mainland China between 2011 and 2019 (data not published), 14 mcr-1 -harboring isolates were detected corresponding to a positivity rate of 0.4%, which could be regarded as a low prevalence rate. Similar results were reported previously for isolates cultured from clinical, food or food-producing animals ( Carnevali et al, 2016 ; Cui et al, 2017 ; Lu et al, 2019 ; Luo et al, 2020 ). Susceptibility testing of CFSA231 and CFSA629 against colistin, recorded MIC values of 2 mg/L, are consistent with mcr-1 mediated low-level colistin resistance (2–8 mg/L) ( Zhang et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…According to our latest data related to more than 3,800 foodborne Salmonella recovered in mainland China between 2011 and 2019 (data not published), 14 mcr-1 -harboring isolates were detected corresponding to a positivity rate of 0.4%, which could be regarded as a low prevalence rate. Similar results were reported previously for isolates cultured from clinical, food or food-producing animals ( Carnevali et al, 2016 ; Cui et al, 2017 ; Lu et al, 2019 ; Luo et al, 2020 ). Susceptibility testing of CFSA231 and CFSA629 against colistin, recorded MIC values of 2 mg/L, are consistent with mcr-1 mediated low-level colistin resistance (2–8 mg/L) ( Zhang et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Globalisation and industrialisation of food production has contributed to the emergence of opportunistic pandemic clones (Anderson, 2010). In this study, all of the 19 monophasic S. Typhimurium strains collected from different stages of the pig production process in Northern Thailand were found belong to ST-34, a globally disseminated, multidrug resistant clone closely associated with industrial livestock infections and is often implicated in human food-borne outbreaks (Gymoese et al, 2017;Luo et al, 2019;Zheng & Feng, 2019). Isolates were collected from different stages of the pork production process in Northern Thailand, all of which were found to have been infiltrated by the ST-34 pandemic clone.…”
Section: Discussionmentioning
confidence: 82%
“…Surprisingly, in this study, only four isolates were observed with either of these resistance mechanisms, including two S. Typhimurium isolates carried mcr-1 and two isolates had missense mutations in pmrAB. According to previous studies in China, S. Typhimurium appear to more easily acquire mcr genes compared to S. Enteritidis (Li et al, 2016;Cui et al, 2017;Luo et al, 2020). This may be because S. Typhimurium in general is more susceptible to colistin than S. Enteritidis, and so tend to acquire mcr genes in order to adapt to colistin selection pressure.…”
Section: Discussionmentioning
confidence: 96%
“…Resistance to polymyxins can be conferred via mutations in chromosomal genes, such as genes involved in the PmrAB/PhoPQ two-component systems, which promote the expression of LPS modification related genes, such as pmrC, pmrE, and pmrHFJKLM operon (Olaitan et al, 2014;Poirel et al, 2017). Plasmid-mediated colistin resistance genes (mcr) have since discovery in 2015 been frequently observed, and their continued widespread dissemination has became a challenge to public health worldwide (Liu et al, 2016;Luo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%